O impacto dos centros de atenção psicossocial-CAPS nas internações psiquiátricas em municípios cearenses - Aquino, Raimundo Alonso Batista de (2003)
Introduction -The Brazilian psychiatric reform movement started at the same time of sanitary reform followed by desinstitucionalization period looking for a society without asylums. New models of mental health care have been created in which Psychosocial Rehabilitation Centers have received greater importance. Objective - This study aims to evaluate the impact of Psychosocial Rehabilitation Centers in psychiatric hospitalizations in cities where they were implemented. Methodology - Data on psychiatric hospitalization authorization from 1995 to 2001 were analyzed taking as reference the two years period before and two years after the implementation of Psychosocial Rehabilitation Centers. Demographic (sex, age), clinicai (diagnoses, time ofhospitalization) and economical data were analyzed. Results - An important reduction in the annual hospitalization rate (18,63%) was observed in all five cities studied. A higher number of hospitalization (58%) was observed in age group between 20 and 39 years in both periods (before and after CAPS). Males had more hospitalizations which had a mean variation of 9% before and 21,12% after the CAPS. Schizophrenia and other schizophrenic spectrum disorder represented 53,85% of hospitalizations before the CAPS implementation reaching 70,27% following this period. Mental disorders related to Chemical substances showed a 10,62% and 13% before and after the CAPS respectively. Affective disorders were the third cause of hospitalization 8,11% and 8,5% before and after CAPS. Schizophrenia spectrum disorder, mental disorders related to Chemical substances and affective disorders represented the three principal diagnostic groups showing the highest psychiatric hospitalization rate (91%) after CAPS. The mean hospitalization time was 30 days. There was no difference in the mean hospitalization time between two periods studied. There was a reduction of 0,3% in the mean annual hospitalization rate per 1000 people after CAPS, it varied between 0,88% to 0,51%. A reduction of 23% in the expenses with psychiatric hospitalization (real values considered) was observed. Conclusion - The results suggested that CAPS is an important Service for mental health, with possible positive influence in health rates.